2020
DOI: 10.1038/s41586-020-2576-2
|View full text |Cite
|
Sign up to set email alerts
|

Dichotomous engagement of HDAC3 activity governs inflammatory responses

Abstract: Histone deacetylase 3 (HDAC3) is unique among the HDAC superfamily of chromatin modifiers that silence transcription through enzymatic modification of histones because interaction with nuclear receptor corepressors (NCoR1/2) is required for engagement of its catalytic activity 1 – 3 . However, loss of HDAC3 also represses transcription 4 – 8 . Here we report that, during lipopolysaccharide (LPS) activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
91
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 52 publications
7
91
1
1
Order By: Relevance
“…Mechanistically, HDAC3 has been shown to repress NF-kB activity by directly deacetylating p65 (1517), although the engagement of this molecular mechanism in vivo has not been widely reported. Repression of NF-kB function by HDAC3 has been observed in macrophages (18), but has not been reported in the many other HDAC3-tissue specific knockouts. We have identified that in both KL and KP NSCLC cells, HDAC3 actively represses the NF-kB/p65 transcriptional program, resulting in repression of the tumor cell senescence program.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…Mechanistically, HDAC3 has been shown to repress NF-kB activity by directly deacetylating p65 (1517), although the engagement of this molecular mechanism in vivo has not been widely reported. Repression of NF-kB function by HDAC3 has been observed in macrophages (18), but has not been reported in the many other HDAC3-tissue specific knockouts. We have identified that in both KL and KP NSCLC cells, HDAC3 actively represses the NF-kB/p65 transcriptional program, resulting in repression of the tumor cell senescence program.…”
Section: Figurementioning
confidence: 99%
“…1a). In the absence of activating ligands, nuclear receptors interact on chromatin with NCoR and SMRT, which dampen gene expression 36,38,39 .…”
Section: Wd40 Repeat-containing Proteinsmentioning
confidence: 99%
See 3 more Smart Citations